Menjembatani Konstitusi dan Penegakan Hukum: Toleransi dan Hak Asasi Manusia dalam Sistem Peradilan di Indonesia - Lusia Pramesti (Doktrin: Jurnal Dunia Ilmu Hukum dan Politik, 2024)
This study aims to analyze the enforcement of law within the limits of religious tolerance based on the criminal justice system and constitutional regulations in Indonesia. It evaluates how individual and environmental factors influence crime and the importance of granting tolerance to offenders who are dependents of their families. Additionally, the study examines the protection of human rights in the context of religious freedom as stipulated in the 1945 Constitution of the Republic of Indonesia. The methodology used is library research, involving the review of journals, legislation, and related materials. The findings indicate that the protection of human rights, including religious tolerance, is crucial for fostering interfaith harmony and maintaining peace within Indonesia's diverse society. The study emphasizes the need for effective constitutional regulations to ensure religious tolerance and social harmony in Indonesia.